Foreign Direct Investment (FDI) and Employment: A Case of Province of Punjab, Pakistan - Sarwar, Naila; Mubarik, Mohammad Shujaat (The Economics and Finance Letters, 2014)
Foreign direct investment is considered a significant source of capital inflows in developing countries. Along with its several impacts, FDI also influences the employment level of the host country. This study investigated the impact of foreign direct investment on employment in the province of Punjab, Pakistan. We employed the annual data from 1984-2010 to test this relationship. The stationary of the variables was checked by applying ADF test. To find the relationship among variables, we applied ARDL approach. We found existence of co-integration between FDI and employment. Results also illustrated a significant long run direct relationship between variables.